Recent Advances on Sorting Methods of High-Throughput Droplet-Based Microfluidics in Enzyme Directed Evolution - Fu, Xiaozhi; Zhang, Yueying; Xu, Qiang; Sun, Xiaomeng; Meng, Fanda (Frontiers in Chemistry, 2021)
Droplet-based microfluidics has been widely applied in enzyme directed evolution (DE), in either cell or cell-free system, due to its low cost and high throughout. As the isolation principles based on the chemical (labeled) or physical (label-free) characteristics in the droplets, sorting method contributes mostly to the efficiency of the whole system. Fluorescence activated droplet sorting (FADS) is mostly applied labeled method but faces challenges of target enzyme scope. Label-free sorting methods show potential to greatly broaden the microfluidic application range. Here we review the developments of droplet sorting methods, including labeled detections (FADS, absorbance activated droplet sorting (AADS)) and label-free detections (electrochemical, mass activated droplet sorting (MADS), Raman activated droplet sorting (RADS), nuclear magnetic resonance (NMR)). We highlight recent cases in the last 5 years in which novel enzymes or highly efficient variants are generated by microfluidic DE.